The pag Gene of pXO1 Is Involved in Capsule Biosynthesis of Bacillus anthracis Pasteur II Strain - Liang, Xudong; Zhu, Jin; Zhao, Zhongzhi; Zheng, Feng; Zhang, Huijuan; Wei, Jianchun; Ji, Yon; Ji, Yinduo (Frontiers in Cellular and Infection Microbiology, 2017)
The poly-γ-D-glutamic acid capsule and anthrax toxins are major virulence factors of Bacillus anthracis. Genes responsible for capsule biosynthesis are located on pXO2, whereas genes encoding the toxins, which are composed of edema factors, lethal factors, and protective antigens (PA), are located on pXO1. In this study, we found that the pag null mutation not only eliminated the production of the protective antigen, it also eliminated the ability of the B. anthracis Pasteur II strain to form capsules. qPCR analysis revealed that the deletion of pag decreased the transcription levels of the capABCD operon and its regulatory genes acpA and acpB. The introduction of the acpA or acpB plasmid complemented the effect of the pag null mutation on capsule formation. Taken together, the above results suggest that PA probably affects capsule biosynthesis by altering the expression of acpA and acpB. In addition, we found that the deletion mutation of pag remarkably attenuated bacterial pathogenicity in a mouse model of infection. Our results indicate that besides encoding the protective antigen, the pag gene of pXO1 is also involved in the modulation of capsule biosynthesis. Our findings provide new insight into the regulation mechanisms of capsule formation in B. anthracis Pasteur II strain.